Physichemical and microbiological attributes of black wildebeest (Connechaetes gnou) muscles - Ndyoki, Fundeka Patience (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScFoodSc)--Stellenbosch University, 2018.